2020
DOI: 10.15403/jgld-2529
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Pancreatic Adenocarcinoma: the Interrelation with Familial History and Predictive Role on Survival

Abstract: Background and Aims: Pancreatic cancer is associated with poor survival and quality of life. In Romania the prognostic influence of known risk factors for pancreatic adenocarcinoma, such as age, smoking, chronic pancreatitis, diabetes mellitus, and obesity is little known. Their importance in developing cancer in families with a history of adenocarcinoma is less studied. This study aims to assess the risk factors in pancreatic ductal adenocarcinoma, in familial pancreatic adenocarcinoma, in neuroendocrine tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Similar to our study results, Tezuka et al 24 reported that the mean age of FPC was higher than that of non‐FPC, but there was no age difference between FPC and non‐FPC in other studies 15,20,22,23,25,26 . The mean age of FPC patients who underwent curative‐intent operation was 75.3 years, which was higher than the results of other previous studies 15,20‐26 (Table 5). In our study, the mean age of FPC patients who underwent curative‐intent operation was significantly higher than the mean age of FPC patients who did not (75.3 ± 4.8 years vs 60.1 ± 11.4 years, P = .002).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to our study results, Tezuka et al 24 reported that the mean age of FPC was higher than that of non‐FPC, but there was no age difference between FPC and non‐FPC in other studies 15,20,22,23,25,26 . The mean age of FPC patients who underwent curative‐intent operation was 75.3 years, which was higher than the results of other previous studies 15,20‐26 (Table 5). In our study, the mean age of FPC patients who underwent curative‐intent operation was significantly higher than the mean age of FPC patients who did not (75.3 ± 4.8 years vs 60.1 ± 11.4 years, P = .002).…”
Section: Discussionsupporting
confidence: 88%
“…The incidence of FPC for all PC patients was lower than 3.5%-8.9% in previous studies. 15,[20][21][22][23] Also the incidence of FPC for PC patients who underwent curative-intent operation was much lower than in previous studies-6.4%-7.3% [24][25][26] (Table 5). However, our results were similar to the prevalence of FPC (2.7%, 34 parents affected by PC among 1254 PC patients) identified in a large national epidemiological study based on the Sweden Cancer Registry conducted by Hemminki and Li.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, universal screening of PC in all elderly patients with NOD is difficult to achieve and not cost effective. In recent years, many studies have proposed different strategies to stratify T2DM groups and facilitate targeted screening (71)(72)(73)(74).…”
Section: Screening Strategies For Early Diagnosis Of Pc In Patients With T2dmmentioning
confidence: 99%
“…Pancreatic cancer is the ninth most common cancer in women and the tenth most common cancer in men [ 49 , 50 ]. The highest number of cases is recorded among the elderly [ 51 , 52 ]. Pancreatic cancer is difficult to diagnose due to the lack of characteristic symptoms [ 53 ].…”
Section: Pancreatic Cancermentioning
confidence: 99%